Cardiac‐diabetes self‐management program for Australians and Taiwanese: A randomized blocked design study. (25th May 2017) - Wu, Chiung‐Jung (Jo); Sung, Huei‐Chuan; Chang, Anne M.; Atherton, John; Kostner, Karam; McPhail, Steven M.
Abstract: Cardiac disease and type 2 diabetes are prevalent diseases globally. Cardiac rehabilitation and diabetes self‐management programs empower patients' self‐management to improve their health outcomes. However, inappropriate delivery modes and continuing low participation rates indicate some programs are less than optimal. A previous study demonstrated the feasibility of incorporating telephone and text messages into a cardiac‐diabetes self‐management program in Australia; however, the program did not specifically address patients' cultural backgrounds. This current study used a randomized blocked design to evaluate short‐term efficacy of the cardiac‐diabetes self‐management program incorporating telephone and text‐messaging across different cultural contexts in Australia and Taiwan in comparison to usual care. No significant differences between groups were observed for outcomes of self‐care behavior, self efficacy, knowledge and health‐related quality of life, with patients in both groups demonstrating improvements. Patient‐reported outcomes indicated some evidence of an interaction effect between country of origin and group allocation. Findings indicated an improved tendency of outcome measures between the baseline and follow‐up assessments within usual care and intervention groups. Further research is required to clarify components of the program work for each cultural group.